Appraising Genji : literary criticism and cultural anxiety in the age of the last samurai - Caddeau, Patrick W., 1965- (Albany, NY : State University of New York Press, 2006)
"Considered by many to be the world's first novel, The Tale of Genji by Murasaki Shikibu is a masterpiece of narrative fiction rich in plot, character development, and compositional detail. The tale, written by a woman in service to Japan's imperial court in the early eleventh century, portrays a world of extraordinary romance, lyric beauty, and human vulnerability. Appraising Genji is the first work to bring the rich field of Genji reception to the attention of an English-language audience. Patrick W. Caddeau traces the tale's place in Japanese culture through diaries, critical treatises, newspaper accounts, cinematic adaptation, and modern stage productions."--BOOK JACKET.
Ch. 1. Heian fantasies : nationalism and nostalgia in the reading of Genji -- Ch. 2. Hagiwara Hiromichi : masterless samurai and iconoclastic scholar -- Ch. 3. From moral contention to literary persuasion -- Ch. 4. Exposing the secrets of the author's brush -- Ch. 5. Ambiguity and the responsive reader -- Ch. 6. Translating Genji into the modern idiom -- App. I. Character glossary of premodern names, titles, and terms in Chinese and Japanese -- App. II. List of major commentaries on Genji.
Includes bibliographical references (pages 195-206) and index.
Print version record.
JSTOR
Keywords: Murasaki Shikibu, -- 978?-; Genji monogatari (Murasaki Shikibu); LITERARY CRITICISM -- Asian -- General